Изменение структуры различных файлов при циклических нагрузках в корневых каналах зубов у лиц молодого возраста (Эндодонтия Today, 2020)
The present research is based on material of examining 120 files in an electronic microscope. It is established, that a damage rate of all used files (Pro Endo К-file, Pro Endo H-file, M-Two, ProFile) during young age persons endodontic tooth processing is insignificant.